The variations in health cost based on the traditional obesity parameters among patients with coronary artery diseases undergoing cardiac catheterization - Islam M. Alhusban; Audai A. Hayajneh; Mohammad Rababa; Raghad Tawalbeh; Esraa A. Al-Nusour; Khalid Al-Mugheed; Samira Ahmed Alsenany; Sally Mohammed Abdelaliem; Eman S. Alsatari (BMC, 2024)
Abstract Background In the literature, obesity has been correlated with coronary artery diseases (CADs) and high health costs. This study aimed to investigate the relationships between obesity parameters and the health costs among patients with CADs undergoing cardiac catheterization. Method A secondary data analysis was done for an original study. The original study was conducted among 220 hospitalized patients undergoing cardiac catheterization from two main hospitals located in the Middle and Northern regions of Jordan. Bivariate Pearson's correlation and forward linear regression analysis were calculated in this study. Results The average health cost for the participants was 1,344 JOD (1,895.63 USD). A significant positive moderate correlation (r = 0.4) was found between hip circumference (HC) and health cost. There were significant positive weak correlations between low-density lipoprotein (LDL), triglycerides, high-sensitivity C-reactive protein (HS-CRP), hemoglobin A1c (HbA1c), and depression, and the health cost (correlation coefficient 0.17, 0.3, 0.29, 0.22 and 0.17, respectively. HC, waist circumference (WC), waist-height ratio (WHtR), waist-hip ratio (WHR), and body adiposity index (BAI) were significantly associated with health costs among male participants. In contrast, among females, none of the obesity parameters was significantly associated with health costs. The forward regression analysis illustrated that an increase of HC by 3.9 cm (β (0.292) * SD (13.4)) will increase the health cost by 1 JOD (0.71 USD). The same analysis revealed that HS-CRP increased by 0.4 mg/dl (β (0.258)*SD (1.43)), or triglycerides increased by 8.3 mg/dl (β (0.241)* SD (34.3)), or depression score increased by 0.32 score (β (0.137)* SD (2.3)), or total cholesterol increased by 4 mg/dl (β (0.163)* SD (24.7)), the health cost will increase by one JOD (0.71 USD). Conclusion Healthcare providers, including nurses, should significantly consider these factors to reduce the health costs for those at-risk patients by providing the appropriate healthcare on time.